Sinergi Antara Fenomena “Tiktok Brain” dalam Pembelajaran Matematika di Sekolah Menengah Pertama - Cuhanazriansyah, Muhammad Rinov; Anggraeni, Risma Dea; Irhadtanto, Boedy (Polinomial : Jurnal Pendidikan Matematika, 2025)
This study aims to analyze the impact of the "TikTok Brain" phenomenon on enhancing mathematics learning at SMP Negeri 1 Kapas. The term "TikTok Brain" refers to students' decreasing attention spans due to frequent exposure to short-form video content on the TikTok platform. the data analysis technique employed a quantitative approach with a quasi-experimental design, specifically a one-group pretest-posttest design. A random sample of 66 seventh-grade students was selected from a population of 193. The research instruments included questionnaires, pre-tests and post-tests, as well as interviews to support qualitative insights. The results indicate that the use of educational TikTok content significantly improved students’ mathematics learning outcomes, as evidenced by the difference between pre-test and post-test scores through a paired sample t-test. Additionally, structured use of TikTok increased student motivation, engagement, and helped address challenges such as reduced attention span and the Fear of Missing Out (FOMO). This study recommends integrating social media as an innovative learning medium aligned with the characteristics of today's digital generation.